Hydrocephalus in primary brainstem hemorrhage risk predictors and management - Yuehui Ma; Linghao Bu; Dengchang Wu; Kang Wang; Hengjun Zhou (Scientific Reports)
Abstract This study explored the risk factors associated with hydrocephalus incidence and evaluated the effectiveness of surgical treatments in managing this condition. Patients with PBSH were retrospectively evaluated, identifying clinical and radiological characteristics. A multivariate logistic regression model was used for analyses. Of the 169 patients studied, 77 developed hydrocephalus. Midbrain hemorrhage, tegmental pons hemorrhage, disappearance of annular cisterna, combined cerebellar and intraventricular hematoma increased the risk of hydrocephalus (p < 0.05). A linear relationship was found between hematoma volume and hydrocephalus, with a volume > 6.1 mL associated with a higher risk. Patients with ≥ 2 the following factors: multiple hematoma sites, intraventricular hematoma, or hematoma volume > 6.1 mL, had a significantly increased risk of hydrocephalus. Forty-seven patients received surgical treatments including stereotactic puncture drainage of hematoma (SPDH) or external ventricular drainage (EVD). Both SPDH and EVD were effective in treating hydrocephalus (p < 0.001). The combination of SPDH and EVD showed the greatest benefit (p < 0.001); 30-day mortality and de-ventilator rates in the surgical group were significantly different from the non-surgical group. This finding provides valuable insights for early surgical intervention in patients with PBSH.